El numerator: material manipulativo para aprender operaciones básicas en el cuarto grado de Educación General Básica. - Zhondo Macas, Anabell Alexandra (2023)
This research work was about the Numerator: manipulative material for learning basic operations in the fourth grade of General Basic Education. The general objective is to determine the importance of the numerator in the learning of basic operations with students of fourth grade at Mushuk Rimak, General Basic Education, of the Intercultural Bilingual Community, during the 2022-2023 school year. The type of study was descriptive with a quasi-experimental design and a mixed approach, the methods were: scientific, analytical, synthetic and statistical which helped to clarify the work of curricular integration, provide a basis for the different postulates of the authors and based on this infer criteria in order to address the increased issue, the target population consisted of seventeen students and a teacher, to collect information a diagnostic evaluation designed based on the contents of the Curriculum of the Ministry of Education and a structured interview with the teacher was applied. The results obtained show that a significant percentage of the students, they do not reach the required learning; therefore, it is necessary to undertake improvement actions for the learning of addition, subtraction and multiplication; for which the alternative proposal "Playing with the Numerator" was planned and successfully executed through a didactic guide. According to the results obtained in the second application, it was determined that the numerator is an excellent manipulative resource for the teaching of addition, subtraction and multiplication, the students understood in a better way the basic mathematical exercises. Therefore, the teacher is encouraged to carry out this and other similar actions to improve the students ́ mathematical knowledge; therefore, student should be registered in courses and constant updates in order to improve the professional practice. Key words: Numerator, learning, basic operations, addition, subtraction, multiplication